(untitled) (Research, Society and Development, 2020)
To compare follicular dynamics after treatment with low doses of equine pituitary extract obtained during winter and summer and to study the relationship between follicular dynamic and environmental parameters, 21 mares were evaluated to follow follicular dynamic and ovulation, from the final of the spring transitional up to the beginning of autumnal transitional period. Mares were randomly designed to one of three treatments: Equine Pituitary Extract from summer (EPE-S), Equine Pituitary Extract from winter (EPE-W) or saline (Control). Treatments were repeated twice: March/2017, after autumnal equinox and April/2017. Temperature, humidity, solar radiation and hours/ light/day were recorded and Temperature Humidity Index (THI) was calculated. Pre-ovulatory follicles reached the greatest diameter (40.7 mm) in December (p<0.05), following the increase in light/hours/day. The smallest pre-ovulatory follicles were verified in February (34.6 mm) and March (35.0 mm) (p>0.05). After EPE, days for ovulation differed, as well as the diameter of pre-ovulatory follicles (p<0.05). EPE-W showed similar follicular dynamics as Control, ovulating smaller follicles (p<0.05) and later (p<0.05) than EPE-S. Temperature and solar radiation did not differ (p>0.05), but humidity and THI differed (p<0.05). THI was not correlated to the diameter of pre-ovulatory follicles (p=0.37), diameter of subordinate follicles (p=0.80), or number/ follicles per ovulatory wave (p=0.98). In conclusion, daylight duration influenced ovarian function; low doses of EPE-S improvede follicular growth and ovulation rate during autumnal transition period of mares; pre-ovulatory follicle diameter increased from the spring to summer, but the time required to reach ovulation decreased.